Evaluation of the Toxicity of Dichlorodiphenyl-trichloroethane (DDT) to the Expression Levels of Three Genes p53, rarα1, wnt in the Embryos and Liver of Fish Medaka Oryzias latipes - Huong, Tran Thi Thu; Tong, Nguyen Xuan (VNU Journal of Science: Natural Sciences and Technology, 2022)
Three genes p53, rarα1, wnt and liver of Medaka fish tissue were selected to study the toxicity of DDT to fish embryo (8 days old) and adult Medaka fish (3 months old). TEM and real-time PCR methods were used to examine changes in structure of liver tissue and genetic expression. The TEM results recorded a clear difference between the control and the experimental sample. Adult Medaka fish exposed to 1µg/L DDT for 24 hours has a distorted liver cell nucleus with many hollow lipid particles, and the sinus-shaped meshes are clustered, interrupted; lysosome is not intact with many degenerative bubbles. The results of real-time PCR analysis showed that DDT affects the development, different and proliferation of cells in the embryonic stage and gene expression in adult stage. All three genes p53, rarα1 and wnt in fish embryos changed strongly and tended to be inhibited when exposuring with 1700µg/L DDT, the values ​​were recorded respectively 0.9; 4.9 and 5.4 times compared to the control sample (1 times). For adult fish, gene expression was lower than fish embryos with real-time PCR analysis values ​​for the three genes p53, rarα1 and wnt respectively 0.9 and 0.5; 0.36 and 0.09; 0.53 and 0.09 times after exposure to 1500 and 1700 µg/L DDT. These results demonstrated that gene expression is dependent on the developmental stage of the cell as well as on the dose of the chemical exposed. The development , cell differentiation/proliferation in the embryonic and adulthood stages affected differently to the cell gene expression.